Autogeny, Fecundity, and Other Life History Traits of Culex pipiens molestus (Diptera: Culicidae) in Shanghai, China. Issue 3 (3rd January 2019) - Gao, Qiang; Su, Fei; Zhou, Yi-Bin; Chu, Wei; Cao, Hui; Song, Li-Li; Zhou, Jian-Jun; Leng, Pei-En
Abstract: Culex pipiens molestus Forskål is common in subterranean and aboveground environments in Shanghai, China. However, little is known about its autogeny, fecundity, and other life history traits. In this study, Cx. p. molestus larvae were collected from four different types of underground parking lots and artificially maintained, without blood feeding, in a laboratory. Life history traits parameters were recorded from the F0 to F9 generation. Culex pipiens molestus from Shanghai can autogenously persist for at least 10 generations, and some females can develop more than one egg batch without blood feeding (oviposition rate in Lot C was >100% in some generations). The average number of eggs per raft produced autogenously ranged from 36.94 to 42.19. The average generation time (GT) ranged from 20.06 to 21.30 d, and the pre-oviposition time (POT) ranged from 2.17 to 12.68 d among the generations. Culex pipiens molestus from the four groups had different autogeny, fecundity, and longevity patterns. This variability may result from genetic polymorphism caused by co-occurrence with other Culex pipiens subspecies (Diptera: Culicidae).